RELEVANSI UU NO 28 TAHUN 2014 TERHADAP PERLINDUNGAN HUKUM HAK CIPTA LAGU ATAS MARAKNYA COVER LAGU DI PLATFORM DIGITAL - Nurhuda, Dede Yuda Wahyu; Puspita, Marisa; Rosidin, Utang (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2022)
Abstract The rapid development of digital platforms both as entertainment media requires humans to be more creative in creating new innovations, especially in the field of music. With the development of social media as a medium for entertainment, starting from Tiktok which is currently popular, YouTube, Instagram, and various other media, apart from having a positive impact, it also has a negative impact, such as copyright infringement with the rise of musicians covering songs on social media who do not know ethics. when using other people's songs that have an impact on the use of songs illegally. Copyright is part of intellectual property rights that should be protected, Indonesia itself has regulations on copyright regulation, namely Law No. 28 of 2014. In this study, the author will delve deeper into the relevance of Law No. 28 of 2014 on